Pengaruh Pemberian Jus Buah Naga Hylocereus Undatus (Haw.) Britt&Rose Terhadap Jumlah Hemoglobin, Eritrosit dan Hematokrit pada Mencit Putih Betina - Arifin, Helmi; Nofiza, Welli; Elisma, Elisma (Jurnal Sains dan Teknologi Farmasi, 2012)
Sub-acute toxicity test of dragon fruit juice has been research Hylocereus undatus (Haw.) Britt. & Rose of with  hematological  parameters to female white mice. Juice given orally by 0,5 mL/20 g of  weight dose with variation are 100%, 50% and 25%, once a day along 7, 14 and 21 days. A female white mice were only given food and water used as comparison. Calculated and measured parameters are levels of hemoglobin, erythrocytes and hematocrit, using tools haemometer Sahli, haemositometer and centrifuge. Results  that given dose of dragon fruit juice Hylocereus undatus (Haw.) Britt. & Rose has been provided the effect to increased hemoglobin and erythrocytes level (p < 0,05), but did not raised the hematocrit level (p > 0,05).